Produção da agricultura familiar no município de Nova Palma – RS – Brasil: uma abordagem na perspectiva do programa nacional de alimentação escolar (PNAE) - Fantineli, Dreisse Gabbi (2017)
The present work has as central theme the production of family agriculture in the municipality of Nova Palma - RS and the National School Feeding Program (PNAE). The general objective of the research was to analyze the social and economic influences of the Program in the municipality. The specific objectives are: a) to show the positive aspects and contradictions of the PNAE and its relation with family agriculture in the municipality; B) identify aspects for the valorization of family agriculture through the PNAE; C) verify the contribution of agricultural products of PNAE in the quality of school meals in the municipal schools; D) determine the contribution of the PNAE in the generation of work and income in family agriculture. Interviews were carried out with the family farmers who participate in the PNAE, with the city's Emater's extensionist, the city's nutritionist and a school lunch-box, in order to be able to view each segment on issues such as: Family farming, the quality of food supplied and food security. The work was carried out in the following stages: bibliographic research, the field work and the analysis and discussion of the results. In the municipality in question, the PNAE contributes to the valorisation and strengthening of family agriculture, generating work and an extra income for the producers. It also contributes to the supply of more natural and less industrialized foods, increasing the quality of school meals in the municipality.